Influence Of Integrated Learning Models Type Connected Assisted Media Images On Results Learning Of Sains - Nurjannah Nurjannah (Publikasi Pendidikan, 2018)
This study aims to determine differences in the learning outcomes of Sains between students who were taught using integrated learning model connected type of image media with students who were taught using direct instruction model (direc instruction). The population of this study is all students of grade IV SD 237 Mattirobulu Pinrang District 2017/2018 lessons year, which amounted to 186 people. Class samples from this research are 28 students of class IVA as the experimental class and students of grade IVB SD Negri 237 Mattirobulu Pinrang District as many as 28 people as a control class selected by drawing. The research design used is a quasi experimental research design with "Non Equivalent Post-test Only Control Group Design" pattern. Student learning result data is obtained by objective test. Data were analyzed by using descriptive statistical analysis technique and inferential statistic that is t-test. The results of this study show that there is a significant difference of learning outcomes between students who are taught using integrated learning model of assisted type of image connected with students who are taught using direct instruction model. The difference is seen from the results of scores of students' learning achievement of Sains obtained tcount is greater than t table (tct = 3.815> ttable = 2.021) at 5% significance level. In other words, the integrated learning model of connected type of media-aided image has an effect on students' learning outcomes compared to direct instruction.Connected Model, Image, Learning Outcomes of Sains